CHDGKB: a knowledgebase for systematic understanding of genetic variations associated with non-syndromic congenital heart disease. (1st July 2020) - Yang, Lan; Yang, Yang; Liu, Xingyun; Chen, Yongquan; Chen, Yalan; Lin, Yuxin; Sun, Yan; Shen, Bairong
Abstract: Congenital heart disease (CHD) is one of the most common birth defects, with complex genetic and environmental etiologies. The reports of genetic variation associated with CHD have increased dramatically in recent years due to the revolutionary development of molecular technology. However, CHD is a heterogeneous disease, and its genetic origins remain inconclusive in most patients. Here we present a database of genetic variations for non-syndromic CHD (NS-CHD). By manually literature extraction and analyses, 5345 NS-CHD-associated genetic variations were collected, curated and stored in the public online database. The objective of our database is to provide the most comprehensive updates on NS-CHD genetic research and to aid systematic analyses of pathogenesis of NS-CHD in molecular level and the correlation between NS-CHD genotypes and phenotypes. Database URL : http://www.sysbio.org.cn/CHDGKB/